2006
DOI: 10.1002/chem.200600891
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Core Twisting on Self‐Assembly and Optical Properties of Perylene Bisimide Dyes in Solution and Columnar Liquid Crystalline Phases

Abstract: A series of highly soluble and fluorescent core-twisted perylene bisimide dyes (PBIs) 3 a-f with different substituents at the bay area (1,6,7,12 positions of the perylene core) were synthesized and fully characterized by (1)H NMR, UV/Vis spectroscopy, MS spectrometry, and elemental analysis. The pi-pi aggregation properties of these new functional dyes were investigated in detail both in solution and in condensed phase by UV/Vis and fluorescence spectroscopy, vapor pressure osmometry (VPO), differential scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
291
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(320 citation statements)
references
References 97 publications
25
291
1
3
Order By: Relevance
“…488 nm) vibronic bands within the S 0 -S 1 manifold. [44][45][46][47] A 0-0/0-1 band ratio close to 1.6 is considered to be monomeric. 45,48,49 Here a 0-0/0-1 band ratio of 1.6 was measured for all four PDI-PAs when dissolved in the solvents from which they were adsorbed to ITO ( Figure S3 in SI), indicating they are essentially fully monomeric prior to film formation.…”
Section: Degree Of Aggregation In Pdi Filmsmentioning
confidence: 99%
“…488 nm) vibronic bands within the S 0 -S 1 manifold. [44][45][46][47] A 0-0/0-1 band ratio close to 1.6 is considered to be monomeric. 45,48,49 Here a 0-0/0-1 band ratio of 1.6 was measured for all four PDI-PAs when dissolved in the solvents from which they were adsorbed to ITO ( Figure S3 in SI), indicating they are essentially fully monomeric prior to film formation.…”
Section: Degree Of Aggregation In Pdi Filmsmentioning
confidence: 99%
“…[1][2][3][4] Perylene diimides (PDIs) derivatives effectively form supramolecular assemblies through p-p stacking interaction. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In particular, supramolecular assemblies based on calixarenePDI conjugates show efficient energy and electron transfer properties due to the well-defined rigid and electron-rich scaffolds of calixarenes. [22][23][24][25][26][27] We have prepared PDI derivatives with a high emission property in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Würthner et al reported that the substitution with bulky groups such as pyrrolidine at the bay area results in the twisting of aromatic core which could hinder a π-π stacking. 18 It is interesting, however, to note that the PBI molecules synthesized in this work still assemble into stacks of columnar aggregates subsequently forming a nematic LC phase due to the hydrophobic nature of the aromatic central core and the hydrophilic periphery. Further characterization of their LC behavior and structural analyses including X-ray diffraction and phase diagram studies are now in progress.…”
mentioning
confidence: 83%
“…For example, Stalke et al 17 reported a series of compounds with different substituents at bay region of perylene core. Würthner et al 18 also reported a series of thermotropic liquid crystals based on PBI dyes with various substituents at the bay area (1,6,7,12-positions of the perylene core). According to their reports, PBI derivatives with electron-donating substituents at the bay area exhibit a large bathochromic shift of the absorption maxima (λmax), reflecting pronounced electronic interactions between the perylene core and the electron-donating groups at the bay area.…”
mentioning
confidence: 99%
See 1 more Smart Citation